Preoperative Embolization Reduces the Risk of Cathecolamines Release at the Time of Surgical Excision of Large Pelvic Extra-Adrenal Sympathetic Paraganglioma. (4th September 2012) - Di Daniele, Nicola; Canale, Maria Paola; Tesauro, Manfredi; Rovella, Valentina; Gandini, Roberto; Schillaci, Orazio; Cadeddu, Federica; Milito, Giovanni
Abstract : A 30-year-old woman with severe hypertension was admitted to the hospital with a history of headache, palpitations, and diaphoresis following sexual intercourse. Twenty-four hour urinary excretion of free catecholamines and metabolites was markedly increased as was serum chromogranin A. Computed tomography scan revealed a large mass in the left adnex site and magnetic resonance imaging confirmed the computer tomography finding, suggesting the presence of extra-adrenal sympathetic paraganglioma. I-metaiodobenzyl guanidine scintigram revealed an increased uptake in the same area. Transcatheter arterial embolization of the mass resulted in marked decreases in blood pressure and urinary excretion of free catecholamines and metabolites. Surgical excision of the mass was then accomplished without complication. Preoperative embolization is a useful and safe procedure which may reduce the risk of catecholamines release at the time of surgical excision in large pelvic extra-adrenal sympathetic paraganglioma.